Efeito da massa do leito na biossecagem pulsante de biomassa de laranja - Bueno, Matheus Rodrigues (Universidade Federal de São Carlos, 2026)
The citrus industry, especially orange production, is highly relevant to the global economic landscape, with Brazil standing out as the leading producer in the 2024/2025 harvest, reaching approximately 13 million tons, representing about 29% of world production. In this context, an important opportunity for improvement in waste management and valorization is evident, since the production of juice and its derivatives generates large quantities of solid waste with high moisture content, intensifying the dependence on drying processes for storage and utilization of these byproducts. Given this scenario, biodrying emerges as a promising alternative for optimizing this process. This study aimed to analyze the effect of different masses of orange solid waste in the bed on the performance of intermittent biodrying with periodic air pulses, seeking to understand the influence of this variable on the process efficiency. The experiments were conducted on a laboratory scale using a fixed-bed biodryer with three masses of residue (2, 4, and 6 kg) and three aeration profiles (15 min/1 h, 15 min/3 h, and 45 min/1 h), maintaining a constant air flow rate of 2.0 m³/h over 72 hours. Temperature and humidity profiles were monitored during the process. The results indicated that beds with higher mass presented higher average temperatures, suggesting greater microbial activity. Regarding humidity, it was observed that the final content was influenced by the degree of contact between the air and the biomass, with better performance associated with longer aeration times. Additionally, it was found that the bed mass impacts the airflow distribution, with bypass observed in beds with lower mass and better air percolation in beds with higher load, which contributed to increased process efficiency.
Effect of bed mass on pulsed biodrying of orange biomass
Keywords: laranja; valorização de resíduos; biossecagem; resíduos de laranja; aeração intermitente; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura